Effectiveness of Empowerment Programme on Stress and Care Giving Burden among Care Givers of Chronically Ill Patients Admitted in MMIMS&R Hospital, Mullana Ambala, Haryana - Shalini Youssouf; Jyoti Sarin; Eenu; Bindu Joseph (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background- One of the most compassionate and self-sacrificing things a person can do is care for a sickloved one. Caring for a family member with impaired mental and behavioral functioning presents the moststressful of care giving situations. Keeping family caregivers healthy and able to provide care is crucial tomaintaining our nation’s long-term healthcare system.Aims – To assess the effectiveness of Empowerment programme regarding stress and care giving burdenamong care givers of chronically ill patients in experimental and comparison group.Material and Methods - A Quasi Experimental non Equivalent control group pretest post test design. 95care givers of chronically ill patients (50 in experimental and 45 in comparison group) selected from hospitalby using convenience sampling technique. Empowerment programme was administered in experimentalgroup. Selected demographic characteristics, standardized perceived stress scale and standardized care giverburden scale were used to collect data.Results- The study showed that the mean post test 1 and post test 2 stress score was 12.44 ± 2.10 &12.26±2.05 and 14.11 ± 3.11 & 14.40± 3.12 in experimental and comparison group respectively. There wasno significant correlation between stress and care giving burden .There was no association of care givingburden score of the care givers in experimental and comparison group with their selected patient demographiccharacteristics and there was no significant association of care giving burden scores with their selected caregiver demographic characteristics in experimental group and in comparison group except gender.Conclusion- Empowerment programme was effective in reducing stress and care giving burden among caregivers of chronically ill patients